Frequency of Donor Deferrals in Blood Bank - Ahsan Zafar, Sidra Khalid, Muhammad Usman Javed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of donor deferrals in blood bank on the basis of questionnaire Methodology: This cross sectional study conducted at Blood Bank, Jinnah hospital, Lahore during 2020-21. All donors were given a questionnaire to fill in. More than 20 questions were given the questionnaire regarding health of the donor before donation. Filled questionnaire was evaluated by researcher herself in order to identify a cause for deferral of blood donation. The donor deferral was then labelled (as per operational definition). Results: Mean age of the participants was 34.15±7.64 years, 147(73.50%) males and 53 (26.50%) females in this study. 18(9%) participants were deferred as donors and 182(91%) participants were not deferred as donors P-0.58. Conclusion: It is concluded that the frequency of donor deferrals in blood bank on the basis of questionnaire is not very high and very much similar to studies conducted in other populations, the reasons fordeferral differ, reﬂecting difference in socioeconomic status. Keywords: Donor Deferrals, blood bank, questionnaire